Estrous synchronization and scheduled artificial insemination for gilts - Davis, Duane L.; Stevenson, Jeffrey S.; Schmidt, W.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Gilts were artificially inseminated on the fifth, sixth and seventh days after estrous synchronization with altrenogest (scheduled AI). Contemporary controls also were synchronized but were checked for estrus twice daily. Scheduled AI gilts had farrowing rates and litter sizes similar to controls. Altrenogest is not presently available to pork producers but these results suggest that it could be used in combination with artificial insemination to schedule breeding according to a predetermined schedule.
Keywords: Swine; Estrous synchronization; Artificial insemination; Gilts